Prediction of major depressive disorder onset in college students - Ebert, David D.; Buntrock, Claudia; Mortier, Philippe; Auerbach, Randy; Weisel, Kiona K.; Kessler, Ronald C.; Cuijpers, Pim; Green, Jennifer G.; Kiekens, Glenn; Nock, Matthew K.; Demyttenaere, Koen; Bruffaerts, Ronny (Depression and anxiety, 2019)
Background Major depressive disorder (MDD) in college students is associated with substantial burden. Aims To assess 1‐year incidence of MDD among incoming freshmen and predictors of MDD‐incidence in a representative sample of students. Method Prospective cohort study of first‐year college students (baseline: n = 2,519, 1‐year follow‐up: n = 958) Results The incidence of MDD within the first year of college was 6.9% (SE = 0.8). The most important individual‐level predictors of onset were prior suicide plans and/or attempts (OR = 9.5). The strongest population‐level baseline predictors were history of childhood–adolescent trauma, stressful experience in the past 12 months, parental psychopathology, and other 12‐month mental disorder. Multivariate cross‐validated prediction (cross‐validated AUC = 0.73) suggest that 36.1% of incident MDD cases in a replication sample would occur among the 10% of students at highest predicted risk (24.5% predicted incidence in this highest‐risk subgroup). Conclusions Screening at college entrance is a promising strategy to identify students at risk of MDD onset, which may improve the development and deployment of targeted preventive interventions.